The Mediating Role of Feelings of Guilt in the Relationship Between Burnout and the Consumption of Tobacco and Alcohol - Olivares-Faundez, V (Blackwell Publishing Ltd, 2014)
Earlier studies have shown that feelings of guilt appear to be involved in the burnout process. However, the exact nature of the relationship between burnout, feelings of guilt, and tobacco and alcohol use is unclear. The purpose of this study was to analyze the role of feelings of guilt in the relationship between burnout and the consumption of tobacco and alcohol. Role conflict, Role clarity, and Feedback were included as predictors of burnout. The sample of this cross-sectional study consisted of 260 Chilean administration and customer service workers. Hypotheses were tested using a path model. The hypothesized model (i.e., Indolence to guilt to tobacco/alcohol use) showed an adequate data fit, including a mediator role of feelings of guilt in the relationship between burnout and alcohol use. The results of this study recommending taking into consideration the evaluation of feelings of guilt as a symptom of burnout in order to develop a more reliable diagnosis of burnout syndrome and its consequences. © Japanese Psychological Association 2014.